Holarrhena parishadii (Apocynaceae), a new species from Palakkad gap of Western Ghats, South India - Ambika, Viswanathan Pillai; Jose, Sojan; Suresh, Veerankutty (Phytotaxa, 2024)
A new species of Holarrhena from the Palakkad gap of Western Ghats, S. India is described and compared with Holarrhena pubescens. Detailed description, distribution, phenology, illustration, key and photographs are provided.